2021
DOI: 10.1242/jcs.258484
|View full text |Cite
|
Sign up to set email alerts
|

Insights into animal septins using recombinant human septin octamers with distinct SEPT9 isoforms

Abstract: Septin GTP-binding proteins contribute essential biological functions that range from the establishment of cell polarity to animal tissue morphogenesis. Human septins in cells form hetero-octameric septin complexes containing the ubiquitously expressed SEPT9. Despite the established role of SEPT9 in mammalian development and human pathophysiology, biochemical and biophysical studies have relied on monomeric SEPT9 thus not recapitulating its native assembly into hetero-octameric complexes. We established a prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 126 publications
(222 reference statements)
1
48
0
Order By: Relevance
“…This is reflected by the concentration dependency of the hexamer curve shifts in our assay. Whether SEPT9 is a bundling factor on its own is currently under debate (Mavrakis et al 2014;Iv et al 2021;. Octamers, but not hexamers have an influence on actin monomer turnover in the elongation phase as detected by our assay.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…This is reflected by the concentration dependency of the hexamer curve shifts in our assay. Whether SEPT9 is a bundling factor on its own is currently under debate (Mavrakis et al 2014;Iv et al 2021;. Octamers, but not hexamers have an influence on actin monomer turnover in the elongation phase as detected by our assay.…”
Section: Discussionmentioning
confidence: 74%
“…The C-terminus of SEPT9 contributes to filament formation Human hexameric septin rods are available for in vitro experimentation and even crystallization since several years (Sheffield et al 2003;Sirajuddin et al 2007). However, purified octameric rods containing also SEPT9 were only very recently obtained (Iv et al 2021). We introduce here an additional simple, two step purification protocol for human octameric rods harboring a hexa-histidine tag at only one of its subunits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many years, the subunit order of the human hexamer (and therefore that implied for the octamer) was erroneously considered to be SEPT7-6-2-2-6-7. New studies have shown the correct order to be SEPT2-6-7-7-6-2 (Mendonça et al, 2019;Mendonça et al, 2021) or SEPT2-6-7-3-3-7-6-2 in the case of octamers (Figure 1B; DeRose et al, 2020;Soroor et al, 2021;Iv et al, 2021).…”
Section: The Septin Hetero-oligomer: the Building Block For Polymerizationmentioning
confidence: 99%